-4х - 3х - 9х = -16х
1,3а - 2а + 6,5а = -0,7а + 6,5а = 5,8а
2,1b + 3,5b - 4,7b = 0,9b
a + 4b - a - 7b = = -3b
-2x + 3,7x + 2x - 5 = 3,7x - 5
<span>6 684:6+5 339 -3*289 = 5586
1) 6684 : 6 = 1114
2) 3*289 = 867
3) 1114 + 5339 = 6453
4) 6453 - 867 = 5586
</span><span>1890*3650 - 9312:388+999 = 6899475
1) 1890 * 3650 = </span>6898500
2) 9312 : 388 = 24
3) 6898500 - 24 = 6898476
4) 6898476 + 999 = 6899475
5,1<span><5,11
67,3</span><span>>67,204
вроде так</span>
ДАНО:
a=(b+c)
(b-4)/(c-4)=3
(a-4)/(b-4)=3
РЕШЕНИЕ:
(b+c-4)/(b-4)=3
b+c-4=3*(b-4)
b+c-4=3b-12
b+c=3b-12+4
b+c=3b-8
c=3b-b-8
c=2b-8
(b-4)/(2b-8-4)=3
(b-4)/(2b-12)=3
b-4=3*(2b-12)
b-4=6b-36
b-6b=-36+4
-5b=-32
b=-32/(-5)
b=6.4 лет среднему
с=2*6,4-8=4,8 лет младшему
а=6,4+4,8=11,2 лет старшему
проверка:
6,4+4,8=11,2
(6,4-4)/(4,8-4)=3
(11,2-4)/(6,4-4)=3
Ответ: среднему 6,4 лет